PRO-ACTIVE PROPOSAL HIRING DISCRIMINATION VERMONT (Tufts Archival Research Center, 2007)
Report summarizing pro-active proposal addressing hiring discrimination in Vermont. Proposes legislation that would prohibit discrimination against smokers in hiring and promotion practices. Cites that the tobacco industry will engage in a defensive strategy such as coalition support, grassroots mobilization and media resources.